(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Atrazine is the second most widely used herbicide in Nigeria, an excellent polluter of surface and ground sources of water; it finds its way into the water bodies through percolation and surface run-off during rainy and dry season farming. The chemical has some effects on the ecosystem especially in aquatic habitats. different concentrations of atrazine have been prepared (0, 1, 2, 3, and 4 mg/l) and each treatment was replicated four times. a total number of twenty-five basins were used. Five test organisms (Clarias garipienus) were used in each basin. During 96-hour exposure, physicochemical parameters, morphological changes and abnormal behavior in the fish were observed. The research also considers biochemical changes in the kidney, liver and gills where the activities of cretinine, Urea, AST, ALT and Total bilirubin was assayed using colorimetric method. Based on the results obtained in this study, atrazine is found to be toxic to Clarias gariepinus. The result of the biochemical parameters and histological assay showed that Clarias gariepinus was seriously affected by atrazine. KEYWORDS